Review of the genus Arhaconortus Belokobylskij, 2000 (Hymenoptera: Braconidae: Doryctinae), with description of three new species from Vietnam - Oanh, Nguyen Thi; Long, Khuat Dang; Hiep, Nguyen Duc; Nghiep, Hoang Thi (Zootaxa, 2023)
In the present study, the genus Arhaconotus is revised and keyed with three species of this genus from Vietnam were described and fully illustrated as new for science, viz. Arhaconotus belokobylskiji Long, sp. nov., A. hoabinhicus Long, sp. nov. and A. longicaudatus Long, sp. nov., and one species, A. hainanensis Tang & Chen, 2010 newly recorded for Vietnam’s braconid fauna. Up to know, a total of seven species of Arhaconotus are described, a key to all the already known Arhaconotus species is provided. Comparative morphological characters of Arhaconotus species were also discussed.